Why neuroendoscopy is not for all supratentorial intracranial arachnoid cysts in children: analysis of risk factors and prognosis - Tiago Paiva Cavalcante; Breno William Mariz Guedes; Dandara Carvalho Moreira (Brazilian Society for Pediatric Neurosurgery, 2022)
Cerebral neuroendoscopy is a minimally invasive approach that reduces brain exposure, retraction and mobilization of neural tissues and neurovascular structures and the treatment of intracranial arachnoid cysts by endoscopy has been widely used. Selection of the patients who are most  likely to benefit remains challenging in certain cases. The purpose of this article is to raise questions and observations regarding its indication and failure in pediatric patients with suprasellar, and middle fossa arachnoid cysts. We searched English-language articles published in the last 20 years and found evidence that Neuroendoscopy emerged as an alternative to the treatment of this pathology and has its definitive role as a safe, less morbid strategy in these supratentorial pediatric arachnoid cysts and must be added to the therapeutic protocols respecting the best indication.